ANALISIS IMPLEMENTASI RENCANA TANGGAP DARURAT (EMERGENCY RESPONSE PLAN) PADA KAPAL PENUMPANG X - Lintang Setyowati; Suroto Suroto; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
Base on the report of work akuntability the govermants on 2013 there were 75 cases of ship accidents happened in Indonesia. The accidents made victim loss and material. To prevent the loss, emergency response plan is needed. Emergency response plan consist of risk assessment, personil, facility of emergency, drills, procedur of emergency, and share of information. Ship safety and security regulated in SOLAS. The X passanger ship is belonge to PT PELNI and it ever had a ground and man over board accident. The aim of this research is to analize the emergency response plan implementation in the X passenger ship.this is descriptive kualitative research with observation and depth interview. The subject was 5 of main informan, and 2 informan triangulation. This researchs result shows that the implementation of emergency response plan on X passenger ship was enough to meet the regulation. Risk assessment has not been applied, but they had did hazard identification. The personil having ability to face emergency.The facility was ready to deal with emergency. The drills that applied has meet the regulation. The information sharing was good, and can support the emergency response plan.